Grain legume seed systems for smallholder farmers: perspectives on successful innovations - Ojiewo, Christopher Ochieng; Omoigui, L.O.; Pasupuleti, J.; Lenné, Jillian M. (SAGE Publications, 2020)
Grain legumes are nutritionally important components of smallholder farming systems in sub-Saharan Africa and Asia. Unfortunately, limited access to quality seed of improved varieties at affordable prices due to inadequate seed systems has reduced their contribution to improving nutrition and reducing poverty in these regions. This paper analyses four seed systems case studies: chickpea in Ethiopia and Myanmar; cowpea in Nigeria; and tropical grain legumes in Nigeria, Tanzania and Uganda highlighting outcomes, lessons learned, and the enabling factors which supported the successful innovations. All four case studies highlighted at least some of the following outcomes: increased adoption of improved varieties and area planted; increased productivity and income to farmers; improved market access and growth; and significant national economic benefits. Important lessons were learned including the value of small seed packets to reach many farmers; the value of innovative partnerships; capacity building of value chain actors; and continuity and coherence of funding through Tropical Legumes projects II and III and the recently funded Accelerated Varietal Improvement and Seed Delivery of Legumes and Cereals in Africa (AVISA) project. Successful adoption of innovations depends not just on the right technologies but also on the enabling environment. The case studies clearly showed that market demand was correctly identified, establishment of successful partners and institutional linkages overcame constraints in production and delivery of improved seed to smallholders, and fostered conducive policies supported national seed systems. All were integral to seed system viability and sustainability. It is hoped that these examples will provide potential models for future grain legume seed systems efforts. In addition, the analysis identified a number of areas that require further research.